The antecedent and consequences of resistance to social media adoption in SMEs - Yuni Istanto; Dyah Sugandini; Mohamad Irhas Effendi; Rahajeng Arundati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to analyze the resistance to social media adoption in SMEs that have limited resources and experienced a decline in sales due to the COVID-19 Pandemic. Social Media adoption resistance is observed from inadequate resources, usage barriers, and weak government support. These SMEs are also faced with the condition that they are forced to adopt S.M. to save their marketing performance which cannot be done conventionally but must utilize digital technology. The research method used is a survey using a questionnaire. The respondents observed were 230 SMEs in the Special Region of Yogyakarta. The data analysis technique uses a structural model approach with SEM-PLS. This research finds that resistance to social media adoption is influenced by a lack of resources and weak government support for SMEs. As a result, the marketing performance of SMEs is declining, and the business innovation model is not working. SMEs remain in a slump if they do not apply digital technology and utilize social media. This original study discusses SMEs still resistant to adopting S.M. The respondents of this research are also SMEs forced to adopt S.M. Respondents are faced with increasingly stringent social and physical restrictions. Respondents are also SMEs affected by the Pandemic and tend to be close to bankruptcy.